Tecnologias CAVE-HOLLOWSPACE para a Mina do Lousal - Costa, V. (2021)
ln the context of project Ciência Viva da Mina do Lousal, we developed an immersive virtual reality environment in which a group of people, for example, students, can visit a mine. This article discusses and rationalizes the diverse technological choices to achieve this task.